Femtosecond laser versus manual clear corneal incision in implantable collamer lens surgery - Zhao-Yang Meng; Lin Yang; Peng Zhou (Scientific Reports)
Abstract This study aims to compare the efficacy and safety of femtosecond laser-assisted implantable collamer lens (ICL) implantation with traditional manual ICL techniques. A retrospective analysis was conducted on patients who underwent ICL implantation at Beijing New Vision Eye Hospital in 2023. Patients (aged 18–45) were matched for gender and refractive error, with forty-two eyes in each group. Preoperative and postoperative parameters were measured at intervals of 1 day, 1 week, 1 month, 3 months, and 6 months post-surgery. Statistical analyses were conducted to compare outcomes between the two groups. Contrary to our expectations, short-term results (within 1 month) for the femtosecond laser-assisted group showed significantly lower visual acuity and higher astigmatism levels compared to the traditional group. Over time, both techniques yielded comparable outcomes in visual acuity and other parameters by 3 and 6 months postoperatively. The predictive accuracy for refraction outcomes remained superior in the traditional ICL group throughout the study period. The femtosecond laser-assisted ICL implantation did not display any significant short-term and long-term advantages over traditional manual ICL implantation methods. Given the increased costs and lack of clear benefits, femtosecond laser-assisted incisions are not recommended for ICL implantation at this time.